‘Ideal victims’ in capital penalty hearings: an assessment of victim impact evidence and sentencing outcomes - Kleinstuber, Ross (Journal of crime and justice, 2020)
Critics have argued that victim impact evidence (VIE) may enhance sentencing biases by encouraging judges and juries to treat some types of victims as worthier than others. Yet, research to date has not utilized trial transcripts to assess differences in the quantity and quality of evidence presented. The current study addresses this gap by utilizing transcripts from Delaware capital sentencing hearings (2001-2011). The results indicated that more VIE witnesses were called and a greater amount of VIE was presented when victims aligned more closely with the cultural stereotype of the ‘ideal victim.’ ‘Ideal victims’ were also more likely to be described as having contributed to the community and to be associated with the judge issuing a death sentence. However, VIE itself, what witnesses said about victims and their characters, was not correlated with sentencing outcomes. These findings suggest that victim attributes rather than VIE may be driving sentencing bias.